Age-Related Neurodegenerative Diseases: A Stem Cell’s Perspective - Calvo, Belén; Schembri-Wismayer, Pierre; Durán-Alonso, María Beatriz (Cells (Basel, Switzerland), 2025)
Neurodegenerative diseases encompass a number of very heterogeneous disorders, primarily characterized by neuronal loss and a concomitant decline in neurological function. Examples of this type of clinical condition are Alzheimer’s Disease, Parkinson’s Disease, Huntington’s Disease and Amyotrophic Lateral Sclerosis. Age has been identified as a major risk in the etiology of these disorders, which explains their increased incidence in developed countries. Unfortunately, despite continued and intensive efforts, no cure has yet been found for any of these diseases; reliable markers that allow for an early diagnosis of the disease and the identification of key molecular events leading to disease onset and progression are lacking. Altered adult neurogenesis appears to precede the appearance of severe symptoms. Given the scarcity of human samples and the considerable differences with model species, increasingly complex human stem-cell-based models are being developed. These are shedding light on the molecular alterations that contribute to disease development, facilitating the identification of new clinical targets and providing a screening platform for the testing of candidate drugs. Moreover, the secretome and other promising features of these cell types are being explored, to use them as replacement cells of high plasticity or as co-adjuvant therapy in combinatorial treatments.